Application of colorimetric sensor in monitoring dissolved CO2 in natural waters. (15th June 2022) - Lee, Ji-yeon; Ko, Kwanyoung; Chung, Haegeun
Abstract: Dissolved CO2 originating from underground structures at high concentrations may pose a threat to public and environmental health. Therefore, a convenient monitoring technique that allows fast detection of dissolved CO2 needs to be developed. In this study, a low-cost colorimetric CO2 sensor was applied for monitoring dissolved CO2 . The sensor is composed of an acrylic reactor, cresol red pH indicator solution, and a gas-permeable membrane, and the performance of the sensor was tested for the detection of dissolved CO2 at the range of 2–800 mg CO2 L −1 . Color change of the detection solution within the sensor was mainly dependent on CO2 dissolved in the water sample. This was analyzed using an RGB program that extracts the red, green, and blue intensity of a target color on a scale of 0–255. Δ GB, an index of CO2 concentration corresponding to the change in intensity of green ( G ) and blue ( B ) extracted by the RGB program, exhibited a linear relationship with dissolved CO2 concentrations ( r 2 > 0.95, p < 0.005). In the field, the sensor was able to measure dissolved CO2 between 10 and 411 mg CO2 L −1 within 1 min. Overall, our CO2 sensor has high potential to be used in detection of dissolved CO2 in groundwater and surface waters. Graphical abstract: Image 1 Highlights: An optical sensor based on a pH indicator was applied in measuring dissolved CO2 . RGB program was used for the quantification of dissolved CO2 . Dissolved CO2 at 2–800 mg L −1 was measured in spring and sea water. The sensor performed successfully in the laboratory and field. Dissolved CO2 in natural waters can be monitored using this cost-efficient sensor.